Field calibration of integrated sensing device for soil and plant monitoring in maize irrigation scheduling - KUMARI, ARTI; SINGH, D.K.; SARANGI, A.; HASAN, MURTAZA (Journal of Soil and Water Conservation, 2024)
Field and laboratory experiments were conducted at the Water Technology Centre, ICAR-IARI, New Delhi, to assess and calibrate an integrated sensing device that combines canopy temperature, air temperature, humidity sensors, and a soil moisture sensor. These components are interconnected through a microcontroller and software to measure and record plant temperature, relative humidity, air temperature, and soil moisture, all of which are crucial for irrigation scheduling. During the field calibration process, the study established a regression relationship between ISDI’s soil moisture probe, TDR, and gravimetric soil moisture content (%v/v) at different soil depths (0-45cm). Additionally, periodic readings from ISDI’s soil moisture and infrared sensor probe were recorded in experimental plots and compared with measurements from TDR and a handheld infrared thermometer, respectively. The calibration of ISDI’s soil moisture data with the gravimetric method yielded R2 values ranging from 0.68 to 0.74, while for TDR, R2 values varied from 0.8 to 0.85 across different soil depths up to 45 cm. Furthermore, the readings of canopy temperature closely matched those from the handheld infrared thermometer as their mean performance was at par at a 5% level of significance indicated by paired ttest. The developed integrated sensing device holds promise for linking soil conditions with plant stress indicators, ultimately facilitating the creation of irrigation schedules tailored to specific crop fields.